“Memórias de um sobrevivente” de Luiz Alberto Mendes: relações de poder e autobiografia - MELO, Solange de Jesus Neves (2020)
This work aims to demonstrate the power relations in the narrative, Memoirs of a survivor (2009), Luiz Alberto Mendes. In this perspective, we attempted to theoretical support in French philosopher Michel Foucault, with emphasis in the book to monitor and punish: The Birth of the Prison (2014). In this way, if held a brief contextualization on the evolution of the punitive power in society, starting from the Middle Ages to the modern era, in order to show how the ways of exercising power were becoming until you reach the most common method of punishment that is the prison, in the interior of a society that became known as the disciplinarian, since the body is transformed into an object and target of power. Thus, it is possible to reflect, on the one hand, about how social relations are permeated with power relations, and about how, on the other hand, these are relations of forces that are scattered throughout the social fabric, although for many people the same may go unnoticed. Such relationships are present in the work of Luiz Alberto Mendes in respect to certain social institutions that use different mechanisms or an instrument of power in order to control and shape the conduct of the subject. Another aspect focused in this study is related to the reading of the novel while belonging to the autobiographical genre. For this reflection, we resorted to the work the autobiographical pact (2014), Philippe Lejeune, striving by traits that characterize the narrative Memoirs of a survivor as belonging to the genus discussed.